1998
DOI: 10.1016/s0304-3959(98)00114-6
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor induced hyperalgesia in the rat hind paw is dependent on circulating neutrophils

Abstract: The mechanisms by which nerve growth factor (NGF) induces thermal hyperalgesia and neutrophil accumulation have been investigated in the rat. Thermal nociceptive thresholds in rat hind paw were measured as the time taken for paw withdrawal from a heat source and neutrophil accumulation was measured in hind paw and dorsal skin samples using a myeloperoxidase assay. NGF (23-80 pmol intraplantar (i.pl.) injection) induced a significant (P < 0.05, n = 6-16) thermal hyperalgesia at 5 h after injection and significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
1
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 37 publications
9
68
1
5
Order By: Relevance
“…NGF does not directly interact with or stimulate GFRα receptors (38). However, in addition to direct sensitization of nociceptors, NGF also acts indirectly through activation of various peripheral cell types and the subsequent release of a host of inflammatory mediators, which in turn, sensitize sensory afferents (12,(39)(40)(41). Several inflammatory conditions stimulate artemin release from a number of peripheral cell types, including keratinocytes, fibroblasts, and immune cells (28,42,43), and we hypothesized that NGF-induced cold allodynia was mediated by NGF indirectly promoting artemin release.…”
Section: Significancementioning
confidence: 99%
“…NGF does not directly interact with or stimulate GFRα receptors (38). However, in addition to direct sensitization of nociceptors, NGF also acts indirectly through activation of various peripheral cell types and the subsequent release of a host of inflammatory mediators, which in turn, sensitize sensory afferents (12,(39)(40)(41). Several inflammatory conditions stimulate artemin release from a number of peripheral cell types, including keratinocytes, fibroblasts, and immune cells (28,42,43), and we hypothesized that NGF-induced cold allodynia was mediated by NGF indirectly promoting artemin release.…”
Section: Significancementioning
confidence: 99%
“…Another very important pathology induced by NGF is thermal hyperalgesia. Injection of NGF into experimental animals induced neutrophil accumulation and hyperalgesia in skin (Bennett et al, 1998). A recent report showed that the involvement of certain integrins, especially the ␤1 subunit, is important in developing mechanical hyperalgesia induced by NGF (Malik-Hall et al, 2005).…”
Section: Journal Of Cell Science 121 (4)mentioning
confidence: 99%
“…Leukotrienes produce hyperalgesia in animals (15,16) and human beings (17), and seem to play an important role in the maintenance of a longlasting nociceptive response (18). 5-Lipoxygenase inhibitors such as L-615,919 or ZM 230487 inhibit the hyperalgesia induced by platelet-activating factor (19) or nerve growth factor (20), respectively.…”
Section: Introductionmentioning
confidence: 99%